Prenatal folate, homocysteine and vitamin B12 levels and child brain volumes, cognitive development and psychological functioning: the Generation R Study. (22nd January 2016) - Ars, Charlotte L.; Nijs, Ilse M.; Marroun, Hanan E.; Muetzel, Ryan; Schmidt, Marcus; Steenweg-de Graaff, Jolien; van der Lugt, Aad; Jaddoe, Vincent W.; Hofman, Albert; Steegers, Eric A.; Verhulst, Frank C.; Tiemeier, Henning; et al.
Abstract: Previous studies have suggested that prenatal maternal folate deficiency is associated with reduced prenatal brain growth and psychological problems in offspring. However, little is known about the longer-term impact. The aims of this study were to investigate whether prenatal maternal folate insufficiency, high total homocysteine levels and low vitamin B12 levels are associated with altered brain morphology, cognitive and/or psychological problems in school-aged children. This study was embedded in Generation R, a prospective population-based cohort study. The study sample consisted of 256 Dutch children aged between 6 and 8 years from whom structural brain scans were collected using MRI. The mothers of sixty-two children had insufficient (<8 nmol/l) plasma folate concentrations in early pregnancy. Cognitive development was assessed by the Snijders-Oomen Niet-verbale intelligentietest – Revisie and the NEPSY-II-NL. Psychological problems were assessed at age 6 years using the parent report of the Child Behavior Checklist. Low prenatal folate levels were associated with a smaller total brain volume ( B –33·34; 95 % CI –66·7, 0·02; P =050) and predicted poorer performance on the language ( B –0·28; 95 % CI –0·52, –0·04; P =0·020) and visuo-spatial domains ( B –0·27; 95 % CI –0·50, –0·04; P =0·021). High homocysteine levels (>9·1 µmol/l) predicted poorer performance on the language ( B –0·31; 95 % CI –0·56, –0·06; P =0·014) and visuo-spatial domains ( B –0·36; 95 % CI –0·60, –0·11; P =0·004). No associations with psychological problems were found. Our findings suggest that folate insufficiency in early pregnancy has a long-lasting, global effect on brain development and is, together with homocysteine levels, associated with poorer cognitive performance.